ETNISITAS DAN AGAMA DI KOTA SURABAYA: INTERAKSI MASYARAKAT KOTA DALAM PERSPEKTIF INTERAKSIONISME SIMBOLIK - Prayitno, Ujianto Singgih; Basundoro, Purnawan (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2015)
This research is motivated by the emergence of various conflicts in various cities in Indonesia which is triggered by the activation of ethnicity and religious stereotypes, either individually or in groups in their social interaction. Surabaya is one of the big cities inhabited by various ethnic and religious and those are potential to cause conflict. This study attempts to highlight how the picture of the interaction and the level of trust among ethnic and religious in the city of Surabaya. This study is expected to provide an overview of vertices that have the potential to create conflicts in the future so that it can be anticipated by the Government. Using qualitative method and symbolic interactionism approach, which assumes that the social reality is a series of events that occur in some individuals in the society and lasted consciously and it is related to gestures, vocal, voice, and body expression, it is concluded that the city is a melting pot where people of various ethnic groups and religions merge into one. The conflict occurred because of the characteristics of the groups in conflict distinguishable in the clarity of boundaries between groups in conflict; and the degree of organization of each group are closely related to patterns of interaction and communication that was developed from two sides.